Test the Causality between Trade, Foreign Direct Investment and Economic Growth by VAR Model - THANONGSACK, Maly; HONGSAKHONE , Soulixay (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study aims to test the relationship between trade, foreign direct investment and economic growth with a VAR model using time series data from 1995-2021. It was found that only the level of delay of trade at lag 1 order and the foreign direct investment in Lao PDR at lag 2 order have a statistical significance level of 0.01 and 0.05 respectively. The gross domestic product that affects foreign direct investment in the same direction with a statistical significance level of 0.1 and trade and foreign direct investment is related to the gross domestic product in the same direction with a statistical significance level of 0.01 and 0.05 respectively. In addition, the Granger correlation analysis shows that foreign direct investment affects trade, but trade does not affect foreign direct investment and gross domestic product does not affect trade, but trade affects gross domestic product (one-way relationship). Gross domestic product has an effect on foreign direct investment and foreign direct investment also has an effect on gross domestic product (two-way relationship).